The mitochondrial S7 ribosomal protein gene: Evidence of gene transfer from the mitochondrion to the nucleus. - Zhuo, Degen. (University of Ottawa (Canada), 1994)
This work was first directed at studying plant mitochondrial gene expression during different early stages of plant development. Because of the approaches used, it also led to the isolation and characterization of new plant mitochondrial genes and in turn that led to the study of gene transfer from the mitochondrion to the nucleus during evolution. Mitochondrial cDNA clone libraries were constructed from mitoplast RNAs of 24 hour germinating wheat embryos and six-day etiolated seedlings. One such cDNA clone was found to share similarity with bacterial and chloroplast S7 ribosomal proteins. This protein is important for ribosome assembly and translation initiation. This single-copy gene (rps7) was found to be actively transcribed and the 5$\sp\prime$ termini of its major transcripts mapped immediately upstream of a repeat element, which also precedes the wheat mitochondrial genes for coxII, orf25 and atp6. The precursor rps7 RNA undergoes C-to-U type of RNA editing at three positions within the coding region and one site unexpectedly decreases amino acid similarity with homologues. This site and the second non-silent one show full editing in RNA from germinating embryos whereas some cDNA clones show incomplete editing for these or the silent site in RNA from etiolated seedlings. The patterns indicate no polarity to the RNA editing process. Sequences homologous to the wheat mitochondrial rps7 gene are present in the rice and pea mitochondrial genomes, but absent from that of soybean. Interestingly, the pea homologue lacks 119 bp of the 5$\sp\prime$ rps7 coding region and it is not present anywhere else in the pea mitochondrial genome nor is the 3$\sp\prime$ coding region transcribed. Therefore, it is a truncated pseudogene. Immediately upstream, there is an open reading frame of 248 amino acids, which is actively transcribed and homologous to the orf228 gene in liverwort mitochondria. The derived protein of this ORF shares similarity with those of the helC genes in Rhodobacter capsulatus and orf263 gene in Bradyrhizobium japonicum. This gene product is believed to be involved in the translocation of heme from the matrix to the intermembrane space in cytochrome c biogenesis. Southern blot analysis showed that there are rps7 homologous sequences present in pea and soybean nuclear DNAs. In order to study them further, pea nuclear DNA, pea cDNA and soybean nuclear DNA libraries obtained from Clontech were screened with the wheat mitochondrial rps7 probes. The potentially positive clones turned out to be yeast-bacterial shuttle vectors (in the case of the pea nuclear DNA library) and mitochondrial DNA contamination (in the pea cDNA library). The potentially positive clones from a soybean nuclear DNA library turned out to contain mitochondrial DNA of the orf228 gene plus a 92 bp DNA sequence homologous to the wheat mitochondrial rps7 gene, although the latter was undetected by Southern hybridization analysis. This work, in addition to identifying and characterizing new plant mitochondrial genes, provides evidence for the recent transfer of functional genetic information from the organelle to the nucleus.
Keywords: Biology, Molecular.